RELASI PUSAT-DAERAH DALAM MENANGANI COVID-19 DI INDONESIA - Tulus Santoso (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2020)
The issue of decentralization has become significant in the handling of COVID-19, especially for countries with large island territories and heterogeneous communities such as Indonesia. This paper presents an analysis of the relationship between the center and the local in dealing with the COVID-19 pandemic in Indonesia by conducting literature studies through books, journals, mass media articles, and sources from the internet. Initially, relations between the center and the regions in tackling COVID-19 showed a strong centralization of authority by the central government. In the end, local governments get a proportional role but still make the government conductor in policy orchestration. Synergies between the central and local governments will be the key to success in dealing with COVID-19 in Indonesia. However, cooperation must build within the framework of the unitary state of the Republic of Indonesia.